STRATEGI CITY BRANDING HUMAS PEMERINTAH KOTA BANDUNG SEBAGAI SMART CITY MELALUI PROGRAM SMART GOVERNANCE - annisa dwi; Dini Salmiyah (PRoMEDIA, 2017)
Increased globalization at the present time requires the municipality to compete against its branding including one of the city is the focus of Bandung smart city. Within three years the city has made to compete in the international arena to represent Indonesia was chosen as a 6th Finalist of the world for innovation Smart City of the World Smart City Organization in Barcelona. Public Relations of the Government of Bandung as a reflection of smart governance that actively provide information and to interact actively with the audience through both online and offline media. Researchers used the constructivist paradigm with the aim of research to find out the city branding strategy undertaken by the Government Public Relations Bandung in realizing smart city through smart governance program. This study uses descriptive qualitative method through interview data collection techniques. The object of this research is the Government Public Relations Bandung. Results of the study revealed that the strategy that is through the integration of online and offline communications through social media publishing, electronic and print, establishing media relations, and performed a special event.   Keyword: public relation, city branding, smart city, smart governance